2010
DOI: 10.1159/000314157
|View full text |Cite
|
Sign up to set email alerts
|

Voice Function and Voice-Related Quality of Life in the Elderly

Abstract: <i>Background:</i> Many studies have referred to the effects of age on voice and the consequences of these changes. However, only little is known about the adverse effects of voice changes on quality of life in the elderly. <i>Objective:</i> This study focuses on self-perception of voice in seniors as assessed by the Voice-Related Quality of Life (V-RQOL) questionnaire, on voice quality as measured by the Dysphonia Severity Index (DSI) and on the correlation between these parameters. &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 55 publications
(41 reference statements)
0
18
0
1
Order By: Relevance
“…Researchers have reported negative selfperceptions and complaints of age-related voice changes in aging individuals, which include difficulties with vocal range and control, pitch, and vocal quality. 4,10,43,44 It has also been proposed that there are social implications of voice changes on the aging individual (eg, decreased longevity of singing abilities, impacts on communicative effectiveness and social interaction). 10,16,21,35,[43][44][45][46] Taking into consideration both the vocal and psychosocial impacts arising from physiological aging, it is important to determine whether these physiological changes can be reversed, or lessened, to mitigate the negative consequences brought about by vocal aging.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported negative selfperceptions and complaints of age-related voice changes in aging individuals, which include difficulties with vocal range and control, pitch, and vocal quality. 4,10,43,44 It has also been proposed that there are social implications of voice changes on the aging individual (eg, decreased longevity of singing abilities, impacts on communicative effectiveness and social interaction). 10,16,21,35,[43][44][45][46] Taking into consideration both the vocal and psychosocial impacts arising from physiological aging, it is important to determine whether these physiological changes can be reversed, or lessened, to mitigate the negative consequences brought about by vocal aging.…”
Section: Introductionmentioning
confidence: 99%
“…Speech changes with age, affecting quality of life 1,2 . Underlying degenerative processes include laryngeal neuromuscular degeneration through atrophy and dystrophy , and edema in the vocal fold cover 3–6 .…”
mentioning
confidence: 99%
“…Still, applying of it helps in understanding the real impact on quality of life that the disease causes in personal, social and professional relationships 14 . Studies are found in the literature using V-RQOL protocol in Parkinson's disease, dysphonia abducting 15 , spasmodic dysphonia 16 in teachers 14,17, choristers 18 , elderly 19,20 and patients after resection of laryngeal tumors T1 and T2 21 . However, there are no studies that used the protocol in subjects with a medical diagnosis of CPD.…”
Section: Resultsmentioning
confidence: 99%